Urgensi Pendidikan Moral Pada Anak (Telaah Konsep Pendidikan Moral dalam Surat Al-Isra’ Ayat 23) - Alamin, Nurul Salis; Nurul Hidayah; An-Nisa’a Nurlaila HSHZ; Haliza Nur Azkya; Nisrina Uswatunnisssa (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2024)
This study aims to analyze the concept of moral education in Islam, with a focus on Surat Al-Isra verse 23. Moral education emphasizes the development of values, ethics, and character in persons, which is an important Islamic moral principles emphasize the value of doing good to parents. The aim of the research is how to identify the ways should be interpreted and implication used to children's moral education of Surah Al-Isra verse 23. To answer this question research, the research method used is library research with the putaka material as the main data source. Data collection related to research is carried out through literature, because this study is related to understanding verses of the Qur’an. The results is there are the relevance of the interpretation of Surah al-Isra' verse 23 to children's moral education as well as implications in the form of the importance of respect for parents, kind and gentle language, not scolding parents, and obedience to Allah SWT. This research is far from flawless, therefore if other researchers discover many flaws in it, they would like to discuss it in greater detail